2005
DOI: 10.1002/hup.726
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and their effect on sleep

Abstract: Given the relationship between sleep and depression, there is inevitably going to be an effect of antidepressants on sleep. Current evidence suggests that this effect depends on the class of antidepressant used and the dosage. The extent of variation between the effects of antidepressants and sleep may relate to their mechanism of action. This systematic review examines randomised-controlled trials (RCTs) that have reported the effect that antidepressants appear to have on sleep. RCTs are not restricted to dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
182
2
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(202 citation statements)
references
References 128 publications
6
182
2
12
Order By: Relevance
“…The results also supported our previous findings about sleep satisfaction in depression (Mayers et al 2003a(Mayers et al , 2003b. In participants without current symptoms of either anxiety or depression, poorer sleep timing perception variance was more likely to be explained if the participant was currently taking an antidepressant (presumably as continuation treatment of depressive illness and/or anxiety disorders) supporting the observation that perceptions of poorer sleep is associated with antidepressant treatment (Mayers & Baldwin 2005). However, it was not possible to verify whether those participants were actually taking antidepressants.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results also supported our previous findings about sleep satisfaction in depression (Mayers et al 2003a(Mayers et al , 2003b. In participants without current symptoms of either anxiety or depression, poorer sleep timing perception variance was more likely to be explained if the participant was currently taking an antidepressant (presumably as continuation treatment of depressive illness and/or anxiety disorders) supporting the observation that perceptions of poorer sleep is associated with antidepressant treatment (Mayers & Baldwin 2005). However, it was not possible to verify whether those participants were actually taking antidepressants.…”
Section: Discussionsupporting
confidence: 87%
“…Typically, depressed individuals describe a range of disruptions to sleep including longer sleep latency, more frequent and longer awakenings, shorter total sleep time, and earlier morning waking, compared to those without depression (Gillin et al 1979). Depression is also associated with irregular rapid eye movement (REM) sleep, including earlier onset and greater density (Reynolds 1987), and many antidepressants suppress REM sleep (Mayers & Baldwin 2005). While sleep disturbances are found in other mental disorders, their magnitude is greater in depression (Benca et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many antidepressants such as monoamine oxidase inhibitors (MAOI), tricyclic antidepressants and also selective serotonin reuptake inhibitors (SSRI) strongly, rapidly and lastingly reduce REM sleep [65,66]. While these antidepressants suppress the absolute and relative REM sleep amount, REM density increases with continued treatment [67].…”
Section: Introductionmentioning
confidence: 99%
“…It is well reported that most antidepressant drugs considerably inhibit REM sleep, thus increasing REM sleep latency or decreasing REM sleep density and duration (Mayers & Baldwin, 2005;Murck et al, 2003;Palagini et al, 2013;Steiger & Kimura, 2010;Thase, 2006;Vogel, Buffenstein, Minter, & Hennessey, 1990). Furthermore, research in humans and animals demonstrates that selective REM sleep deprivation can produce rapid antidepressant effects (Benedetti & Colombo, 2011;Maturana et al, 2015).…”
Section: Figmentioning
confidence: 99%
“…Research which demonstrates that many compounds with antidepressant properties suppress REM sleep (Mayers & Baldwin, 2005;Steiger & Kimura, 2010; also see: Murck et al, 2003;Nofzinger et al, 1995;Sonntag et al, 1996), considered alongside evidence that REM sleep duration and density is associated with the consolidation of negative memories (Gilson et al, 2015;Groch et al, 2015;Nishida et al, 2009;Payne et al, 2012;Wagner et al, 2001;Wiesner et al, 2015), has led researchers to speculate that REM sleep alterations may underlie the emotional memory bias observed in depressed patients (Walker & van der Helm, 2009;Walker, 2009). However, the majority of studies directly investigating the effect of REM sleep on emotional memory consolidation focus exclusively on comparisons between recognition performance for neutral and negatively salient stimuli (however see : Cairney, Durrant, Power, & Lewis, 2015), ignoring the possibility that REM sleep may also play a role in the consolidation of positive memories.…”
Section: The 'Affect Tagging and Consolidation' (Atac) Modelmentioning
confidence: 99%